Negation in the language of theology – some issues - Olszewski, Adam (Philosophical Problems in Science (Zagadnienia Filozoficzne w Nauce), 2018)
The paper consists of two parts. In the first one I present some general remarks regarding the history of negation and attempt to answer the philosophical question concerning the essence of negation. In the second part I resume the theological teaching on the degrees of certainty (notae theologice) and point to five forms of negation – known from other areas of research -- as applied in the framework of theological investigations.
Keywords: logic; theology; negation; difference; negation-as-failure; strong negation; imperative negation; notae theologice